Effects of Using Project Work in English Oral Presentation to Promote Undergraduate Students’Speaking Ability - Intasuk, Busarakham; Pengsri, Narithaya; Poomchaiya, Pornchonnee (Journal of Graduate MCU KhonKaen Campus, 2022)
The purposes of this research were to study learners’ English oral presentation after using project work and to assess the project work instruction to promote undergraduate students’ speaking ability. The population was 57 undergraduate students, Faculty of Education who enrolled in Thai Study in second semester of the academic year 2020. The research instruments consisted of 3 lesson plans using project work, English speaking evaluation form and learners’ questionnaires for using project work to promote undergraduate students’ speaking ability. The data collected were analyzed for mean, standard deviation, and percentage. The result of this reserch revealed that the students’ speaking ability increased at significant level of 0.5 after they learned through the project work.